2019
DOI: 10.1029/2019gl083306
|View full text |Cite
|
Sign up to set email alerts
|

The Aleutian Low‐Beaufort Sea Anticyclone: A Climate Index Correlated With the Timing of Springtime Melt in the Pacific Arctic Cryosphere

Abstract: Early and late extremes in the timing of snowmelt have recently been observed in the Pacific Arctic. Subseasonal‐to‐seasonal forecasts of this timing are important for industry, environmental management, and Arctic communities. In northern Alaska, the timing is influenced by the advection of marine air from the north Pacific by the Aleutian Low, modulated by high pressure centered in the Beaufort Sea. A new climate index that integrates their interaction could advance melt predictions. We define this index bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…This is a surprising finding as storm tracks tend to be strongest in winter and stations in the Alaska interior near the B‐C site receive the bulk of their precipitation in summer (Bieniek et al, ). Recent studies have focused on the springtime dynamics in the western Arctic, including the influence of the Aleutian Low on Bering Strait inflow and Alaska snowmelt (Cox et al, ) and the influence of clouds on sea ice extent (Huang et al, ). Focusing on two of the extremes, the spring of 1996 demonstrates a warm scenario wherein B‐C δ 18 O is enriched, sea ice area is reduced, and Bering Strait waters are warmer; while the spring of 1999 represents the colder counterpart (asterisks in Figures c and d).…”
Section: Resultsmentioning
confidence: 99%
“…This is a surprising finding as storm tracks tend to be strongest in winter and stations in the Alaska interior near the B‐C site receive the bulk of their precipitation in summer (Bieniek et al, ). Recent studies have focused on the springtime dynamics in the western Arctic, including the influence of the Aleutian Low on Bering Strait inflow and Alaska snowmelt (Cox et al, ) and the influence of clouds on sea ice extent (Huang et al, ). Focusing on two of the extremes, the spring of 1996 demonstrates a warm scenario wherein B‐C δ 18 O is enriched, sea ice area is reduced, and Bering Strait waters are warmer; while the spring of 1999 represents the colder counterpart (asterisks in Figures c and d).…”
Section: Resultsmentioning
confidence: 99%
“…The rapidly changing high‐latitude climate has made statistical modeling of the high latitudes more complicated. Cox et al () propose a climate index that includes metrics sensitive to linkages to midlatitude variability that addresses some of these issues.…”
Section: Advances In Understanding S2s Predictability and Skillmentioning
confidence: 99%
“…In light of increasing evidence from both data and models for a modern connection between North Pacific circulation and Arctic sea ice (5)(6)(7)(8), as well as the demonstrated influence of North Pacific (15,16,18) and Arctic (13,19) ocean−atmosphere systems on past and present terrestrial hydroclimate conditions, it appears that northern Alaska lies at a climatological crossroads within the western Arctic. This means that paleoclimate records from Arctic Alaska are especially well situated for studying the effects of both changing Arctic sea ice and North Pacific circulation.…”
Section: Significancementioning
confidence: 99%
“…These reductions in sea ice are projected to continue in future decades (3) and have important implications for Arctic terrestrial hydroclimate, as sea ice extent and duration impact the seasonality, type, and amount of precipitation in this region (4). Recent studies have also suggested teleconnections between the extent and duration of Arctic sea ice and midlatitudinal storm tracks (5,6), as well as synoptic-scale processes involving the Aleutian Low atmospheric pressure cell (AL) (7,8) and ocean−atmosphere circulation in the Bering Strait (9)(10)(11), which might link North Pacific hydroclimate directly to changes in Arctic sea ice. While recent observations show the influence of North Pacific climate on Arctic sea ice, little is known about their long-term dynamics or their coupled influence on hydroclimate in the western Arctic.…”
mentioning
confidence: 99%